Assessment of the resource potential of agricultural production and determination of the level of efficiency of its use (on the example of regions of the Republic of Kazakhstan) - Naukenova, B.; Pyagay А. (BUKETOV BUSINESS REVIEW, 2020)
Object: the resource potential assessment (natural, labor, material and technical, etc.) of the Republic of Kazakhstan agricultural sector and the determination of constraining factors for its development. Methods: 1. Economic assessment of land and material resources, the amount of which is presented as an indicator of the resource supply farms. 2. Economic and statistical methods reflecting the link between productive resources and production results. 3. Index methods for assessing resource potential, taking the characteristics of its constituent elements. Findings: 1. Assessment of the agricultural land productive capacity was carried out through the indicator of the agricultural production annual volume in all categories of farms in accordance with its cadastral value per 1 ha, as well as crop production per 1 ha of arable land using the index method. 2. Assessment’s the agricultural production resource potential includes the consistent assessment: first, resources availability, then the agricultural production economic efficiency and, finally, the resource use efficiency in the agricultural production subjects. Conclusions: It was defined the resulting indicators complex, which reflecting the availability’s level of agricultural production resources in the regions, including 10 indicators.